2012
DOI: 10.1371/journal.pone.0035076
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Age Related Variability in Nitrogen, Mobile Carbohydrates, and δ13C within Pinus koraiensis Tree Crowns

Abstract: For both ecologists and physiologists, foliar physioecology as a function of spatially and temporally variable environmental factors such as sunlight exposure within a tree crown is important for understanding whole tree physiology and for predicting ecosystem carbon balance and productivity. Hence, we studied concentrations of nitrogen (N), non-structural carbohydrates (NSC = soluble sugars + starch), and δ13C in different-aged needles within Pinus koraiensis tree crowns, to understand the needle age- and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
(117 reference statements)
3
18
1
1
Order By: Relevance
“…Additionally they found that foliar concentrations of P and other rock-derived minerals varied strongly with site, while nitrogen concentrations varied little; soluble carbon, structural and defensive traits hardly varied between sites; and pigment (in their case just chlorophyll) was the least predictable of traits, probably because photosynthesis is rapidly up-and downregulated in response to light in the environment among other factors . Similarly, δ 13 C is known to vary strongly with light and relative humidity (Buchmann et al, 1997;Yan et al, 2012), which may be why species and soil explained little of its variance in our study. These parallels between tropical and temperate systems suggest broad similarities in plant responses to soil across different regions that differ greatly in temperature.…”
Section: Patterns Of Variation In Leaf Traitsmentioning
confidence: 64%
“…Additionally they found that foliar concentrations of P and other rock-derived minerals varied strongly with site, while nitrogen concentrations varied little; soluble carbon, structural and defensive traits hardly varied between sites; and pigment (in their case just chlorophyll) was the least predictable of traits, probably because photosynthesis is rapidly up-and downregulated in response to light in the environment among other factors . Similarly, δ 13 C is known to vary strongly with light and relative humidity (Buchmann et al, 1997;Yan et al, 2012), which may be why species and soil explained little of its variance in our study. These parallels between tropical and temperate systems suggest broad similarities in plant responses to soil across different regions that differ greatly in temperature.…”
Section: Patterns Of Variation In Leaf Traitsmentioning
confidence: 64%
“…For both ecologists and physiologists, foliar morphology and anatomy are important for understanding the physiology of the whole tree (Yan et al 2012). The control of leaf size, and, by extension, leaf form, is a principle way in which plants adapt to environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…herbivory). For example, differences in the sun exposure and age of leaves can lead to marked differences in SLA, δ 13 C, and N concentration within a tree crown (Mediavilla & Escudero, 2003;Cavender-Bares, Keen & Miles, 2006;Yan et al, 2012;Legner, Fleck & Leuschner, 2014). Trait values of an individual plant vary across the season due to environmental tracking (sensu Bazzaz, 1996) including predictable shifts with phenology (Donohue et al, 2007;McKown et al, 2013) and acclimation to cold temperatures (Wisniewski et al, 1996;Cavender-Bares et al, 2005).…”
Section: (1) How Is Variation In Traits Distributed Across Different mentioning
confidence: 99%